Nucleotide-binding domain-like receptor protein 3 inflammasome contributes to vascular endothelial barrier dysfunction and shock after burn injury - Yu, Huilin; Lyu, Fengjie; Cheng, Zhe; Luo, Minghao; Sasmita, Bryan Richard; Lan, Yuan; Lv, Dingyi (Burns, 2025)
Burn injury-induced systemic inflammation significantly contributes to vascular endothelial dysfunction and hypotension. This study aimed to investigate the role of the nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome in vascular endothelial barrier dysfunction following burn injury. A 30 % total body surface area burn mouse model was established, and MCC950, a specific NLRP3 inhibitor, was administered (10 mg/kg) before and after burn injury. Serum collected from burned rats (burn serum, BS) at one day post-injury was applied to human acute mononuclear leukemia cells (THP-1) and human umbilical vein endothelial cells (HUVECs), with or without 10 μM MCC950. Blood pressure, 72-hour survival rates, serum levels of inflammatory cytokines (IL-1β and IL-18) and L-lactic acid (L-LA), and Evans blue staining of mesenteric arteries were measured. Protein expression of endothelial junction protein (VE-cadherin, ZO-1, occludin), MMP-9, NLRP3 inflammasome components (NLRP3, ASC, cleaved caspase-1), and pyroptosis executioner protein (N-terminal fragment of the gasdermin D protein, GSDMD-N) were examined both in vivo and in vitro. Cell viability and morphological changes of HUVECs, and inflammatory cytokines concentrations in THP-1 cell supernatants were also assessed. Burn injury significantly enhanced Evans blue extravasation in mesenteric arteries, and increased serum inflammatory cytokine and L-LA levels, accompanied by reduced blood pressure and decreased 72-hour survival rates in vivo. Burn injury or BS exposure led to decreased endothelial junction protein expression and increased expression of MMP-9, NLRP3 inflammasome components, and GSDMD-N both in vivo and in vitro. Furthermore, BS exposure resulted in reduced cell viability and evident pyroptotic morphology in HUVECs, along with elevated inflammatory cytokines in both the supernatants and lysates of THP-1 cells. Treatment with MCC950 effectively reversed all observed changes except for the protein expression of NLRP3 itself. In burn injury, activation of the NLRP3 inflammasome is associated with enhanced inflammatory responses and endothelial cell pyroptosis, which may contribute to endothelial barrier dysfunction and the progression of shock. •NLRP3 inflammasome triggers monocyte pyroptosis and amplifies inflammation after burn.•NLRP3 inflammasome promotes endothelial cell pyroptosis after burn injury.•These effects increase vascular leakage and induce burn-induced shock.